Longitudinal reciprocal effects between teachers’ judgments of students’ aptitude, students’ motivation, and grades in math - Reschke, Katharina; Steinmayr, Ricarda; Spinath, Birgit (Contemporary educational psychology, 2019)
We investigated whether teachers’ judgments of students’ aptitude had reciprocal effects on students’ motivation and math grades. We expected that teachers’ judgments of students’ aptitude would predict students’ grades and motivation, and that teachers’ judgments would also be predicted by these two aspects. A sample of N=519 elementary school students was investigated at four measurement occasions from the end of third until the end of fourth grade. Students reported their self-concepts and intrinsic task values in math. Teachers (N=27) judged students’ aptitude in math and provided students’ math grades. Cross-lagged panel analyses revealed that students’ prior grades and prior self-concepts (but not intrinsic task values) had positive effects on teachers’ subsequent judgments of student aptitude. Also, teachers’ prior judgments of student aptitude predicted students’ subsequent grades but not motivation. The findings underscore the importance of teachers’ judgments for students’ achievement development and give insights into which students’ motivational variables influence teachers’ perceptions of students’ aptitude.